Effect of the rapid increase of salinity on anoxic-oxic biofilm reactor for treatment of high-salt and high-ammonia–nitrogen wastewater. (October 2021) - Ji, Bixiao; Zhang, Huining; Zhou, Lun; Yang, Jing; Zhang, Kefeng; Yuan, Xin; Ma, Jianqing; Qian, Yongxing
Graphical abstract: Highlights: R1 excelled at NH4 + -N removal (95%, 60 ~ 70 mg/(L·d)) at 60 g/L salinity. Excessive COD, not salinity, inhibited the nitrification capacity of biofilm. The EPS content of biofilm depended on the capacity to remove organic matter. SND Pseudomonas and Thauera were enriched in the three reactors. The sulfur cycle in reactor might be prevent by controlling the organic load. Abstract: The washing wastewater from the desulfuration and denitration of power plants has high salt (chloride and sulfate) and ammonia–nitrogen concentrations and is difficult to treat using microbiological methods. A novel anoxic/oxic biofilm process was developed to remove ammonia from wastewater. Three rapid strategies (sulfate concentration was increased from 0 to 60 g/L in 6, 13, and 22 days (R1, R2, and R3, respectively)) were applied and produced biofilm with the same nitrification capacity as slow strategies (100–203 days). Excessive organics inhibited the nitrification capacity of the biofilm. R1 excelled at ammonia removal (from 30% to 95%, 70 mg/(L·d), with an effluent ammonia concentration of 4 mg/L) at 60 g/L salinity after the organic load was reduced. The content of extracellular polymeric substances in biofilm depended on its capacity to remove organics. Pseudomonas and Thauera were enriched in the three reactors. Controlling the organic load might prevent the sulfur cycle.